Clinical Outcomes With Once‐Weekly Insulin Icodec Versus Once‐Daily Insulin Glargine U100 in Insulin‐Naïve and Previously Insulin‐Treated Individuals With Type 2 Diabetes: A Meta‐Analysis of Randomised Controlled Trials - Mushood Ahmed (19231379) (2024)
Aims The once‐weekly insulin icodec, a new basal insulin analog, may positively support a reduction in injection frequency and improve adherence to therapy in type 2 diabetes (T2D). This study aimed to evaluate the safety and efficacy of insulin icodec compared with those of once‐daily glargine U100. Methods A comprehensive literature search was conducted using PubMed/MEDLINE, Embase and the Cochrane Library from inception till September 2023. Data about clinical outcomes in both groups were extracted. Forest plots were generated using the random‐effects model by pooling odds ratios (ORs) and mean differences (MDs). Results Five randomised controlled trials and 2019 individuals with T2DM were included. In the pooled analysis, time in range was significantly higher (MD = 4.35; 95% CI: 1.65 to 7.05; p = 0.002) in the icodec group than in the once‐daily glargine group. The HbA1c levels were significantly reduced (MD = −0.13; 95% CI: −0.24 to −0.03; p = 0.02) in the weekly icodec group compared with those in the once‐daily glargine group. The weight gain was significantly less in the glargine group than in the weekly icodec group (MD = 0.41; 95% CI: 0.04 to 0.78; p = 0.03); however, in the subgroup analysis, this change became statistically insignificant in both insulin‐naïve and previously insulin‐treated individuals. The results were comparable across two groups for fasting plasma glucose levels, hypoglycaemia alert (Level 1), clinically significant (Level 2) or severe hypoglycaemia (Level 3), and adverse events. Conclusion Insulin icodec was associated with a reduction in glycated haemoglobin levels and higher time in range, with a similar safety profile as compared to insulin glargine U100. However, further evidence is still needed to reach a definitive conclusion. Other Information Published in: Endocrinology, Diabetes & Metabolism License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/edm2.480